Search for dwarf galaxies in the southwestern sector of the local cosmic void - Popova, A. A.; Karachentsev, I. D
We performed a search for new dwarf galaxies in a direction towards the southwestern part of the Local Void using the data on DESI Legacy Imaging Surveys. In a sky area of ~1000 square degrees, we discovered 12 candidates to nearby dwarfs with a high confidence. Four of them are probable new companions to the nearby galaxy M83 and others are isolated objects. We found also 20 nearby dwarf candidates with a low confidence. Almost all of the detected galaxies are classified as late type dwarfs. A new cluster of bluish stars with an angular diameter of 0'.9 is revealed by us at a high galactic latitude, b = 29o. Being at a distance of ~70 kpc, it can be a globular cluster associated with the Milky Way stellar stream Sagittarius dSph or a new ultra-faint satellite of the Milky Way.
Keywords: Galaxies